Development of an Offline Mobile Application for Enhanced Access to Electrical Standards - Karl Tristan Beroy; Vince Carlos; Michael Angelo Dinio; Doc Alwin Dizon; John Luigi Flores; Errol M. Canlas (Universitas Komputer Indonesia, 2025)
This study developed an offline mobile application providing categorized, searchable access to essential electrical standards, including the Philippine Electrical Code (PEC 1) and selected international guidelines (ICC, NEMA, NETA, NECA). Designed specifically for electrical engineering students and practitioners, the app ensures reliable offline access to crucial references. A developmental research design guided the prototype's creation, utilizing the Input-Process-Output (IPO) conceptual framework. Usability was evaluated through a questionnaire measuring perceived usefulness and ease of use among 30 licensed electrical engineers in Pampanga. Participants reported high satisfaction levels, particularly regarding the application's accessibility and user-friendly interface. Future iterations should incorporate additional technical standards to further enhance the platform's comprehensiveness.